Answer:
3x^6 - 4x^5 + 2x^4
Step-by-step explanation:
Given
-5x^4 ( -3x^2 + 4x - 2)
Step 1 : open the bracket with -5x^4
-5x^4 * -3x^2= 15x^6
Hint: - * - = +
x^4 * x ^2 = x^ 4+2 = x^6
-5x^4 * + 4x = - 20x^5
Hint: - * + = -
x^4 * x = x^4 + 1 = x^5
(x is always raise to the power of 1 but we don't write it or less it is greater than 1 e.g. 2 , 3 ,4, ..........)
-5x^4 * -2 = 10x^4
Hint: - *- = +
Let's combine the answers
15x^6 - 20x^5 + 10x^4
We can look for a factor that can go through as in that can divide all without a reminder
Factors of
15 - 3 * 5
1 * 15
20 - 4 *5
2 *10
1 * 20
10 - 2*5
1 * 10
Since the factor of 5 is common in all, so we are using 5 to divide through
15x^6 - 20x^5 + 10x^4
Using 5 to divide through
15x^6 / 5 - 20x^5 / 5 + 10x^4 / 5
= 3x^6 - 4x^5 + 2x^4